Effects of feeding dry glycerol on milk production, nutrients digestibility and blood components in primiparous Holstein dairy cows during the early postpartum period - Kafilzadeh, Farokh; Piri, Vahid; Karami-Shabankareh, Hamed (Spanish Journal of Agricultural Research, 2015)
The aim of this study was to evaluate the glucogenic property of glycerol supplementation in the dairy cow’s diet. Sixty primiparous cows (control, n=30, and glycerol supplemented, n=30) were used to measure milk yield and components, blood hormone and metabolite profiles, and body condition score. Feed intake and apparent total-tract digestibility were also measured using 10 primiparous cows (control, n=5, and glycerol supplemented, n=5). Dry glycerol was top dressed at 250 g/day/cow from parturition to 21 days postpartum. Average feed intake, milk yield and components were not affected by glycerol supplementation. Apparent total–tract digestibility of organic matter and neutral detergent fibre were not influenced by dry glycerol supplementation, but lipid digestibility was greater (p=0.01) in cows fed glycerol. The serum concentration of glucose and insulin tended to be higher in dry glycerol-supplemented cows (p=0.1; p=0.06, respectively). While, serum concentrations of nonesterified fatty acids and β-hydroxybutyrate were not affected. Supplemented cows had lower body condition loss during weeks 1 to 5 after calving (p=0.09). The glucogenic effect of glycerol did not affect milk yield during the first 3 weeks of lactation. However, daily milk yield during the 13 weeks recording period was higher in the glycerol-supplemented cows (28.5 vs. 30.3 kg, p<0.001). Percentages of cows cycling at the planned breeding date was greater (p=0.01) for cows fed dry glycerol. The results demonstrated that feeding dry glycerol as a glucogenic supply could be useful in saving body reserves and improving energy balance of primiparous Holstein dairy cows during the early postpartum period.